Multiagent Systems Protection. (15th August 2011) - Muñoz, Antonio; Anton, Pablo; Maña, Antonio
Abstract : Agent-systems can bring important benefits especially in applications scenarios where highly distributed, autonomous, intelligence, self-organizing, and robust systems are required. Furthermore, the high levels of autonomy and self-organizations of agent systems provide excellent support for developments of systems in which dependability is essential. Both Ubiquitous Computing and Ambient Intelligence scenarios belong in this category. Unfortunately, the lack of appropriate security mechanisms, both their enforcement and usability, is hindering the application of this paradigm in real-world applications. Security issues play an important role in the development of multiagent systems and are considered to be one of the main issues to solve before agent technology is ready to be widely used outside the research community. In this paper, we present a software based solution for the protection of multiagent systems concentrating on the cooperative agents model and the protected computing approach.